2021
DOI: 10.1002/micr.30800
|View full text |Cite
|
Sign up to set email alerts
|

The use of free myocutaneous flap and implant reinsertion for staged cranial reconstruction in patients with titanium mesh exposure and large skull defects with soft tissue infection after cranioplasty: Report of 19 cases

Abstract: Background Management of cranial defects following failed cranioplasty due to titanium mesh exposure and infection is challenging. The purpose of this report is to describe a modified technique using a free myocutaneous flap transfer for primary soft tissue reconstruction, and titanium mesh reinsertion for cranioplasty revision. Methods Nineteen patients with titanium mesh exposure and infection following cranioplasty were treated from January 2012 to January 2019. The average patient age was 41.89 years and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 23 publications
0
31
1
Order By: Relevance
“…[26,29] Despite the reliability of free flap reconstruction for scalp defects, iatrogenic alopecia and the bulky contour are the most concerning issues. [10,[26][27][28][29] A thorough preoperative discussion and consultation are required to establish rapport with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[26,29] Despite the reliability of free flap reconstruction for scalp defects, iatrogenic alopecia and the bulky contour are the most concerning issues. [10,[26][27][28][29] A thorough preoperative discussion and consultation are required to establish rapport with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The cutting area should be at least 30% larger than the defect area as there will be some degree of contracture after dermis cutting (3). It is better to use an electronic or pneumatic scalpel to cut the dermis so that the obtained dermis will be relatively flat and uniform in thickness; (4). The dermal tissue transplanted on the surface of titanium mesh should not contain an epidermis, and the scope of dermal transplantation should exceed 0.5 cm of titanium mesh.…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated operations not only increase the medical expenses, life, and psychological burden of patients but also increase the risk of titanium mesh exposure(Q2).To close the wound and effectively preserve the titanium mesh, clinicians have achieved certain efficacy through local rotating flaps, fascial flap transplantation, or free skin grafting and free flaps. 4 Researchers reported that an acellular dermal matrix can prevent titanium mesh exposure during cranioplasty and can also be used as a biological mesh to avoid direct contact between cerebrospinal fluid and surface repair tissue, which is conducive to wound repair. 5 However, the high cost of acellular dermal matrix prevents it from being widely used in clinical practice.(Q1)From January 2019 to January 2022, the authors treated 8 patients with titanium mesh exposure after skull repair.…”
Section: Introductionmentioning
confidence: 99%
“…Large skull bone defects complicated with traumatic brain injury are life-threating events in clinical settings. , A defected bone with the two ends in a distal distance is difficult to heal, and edema of injured brain tissues would increase intracranial pressure (ICP), which leads to reduction of cerebral blood flow supply and aggravates brain damages. , To handle these problems, two-stage clinical therapy with craniotomy and cranioplasty was proposed. First, fractured bones were removed, and then skull reconstructive surgery was performed by using synthetic materials such as titanium mesh and polyetheretherketones (PEEK) mesh after a range of several weeks to even one year until the edema disappeared. However, during the long interval between these two phases, effective temporarily protective biomaterials are lacking, which should present antibacterial ability, satisfactory mechanical strength, structural stability, and biocompatibility to safeguard the brain, prevent potential infections, and improve cosmetic effects. In recent years, even though single-stage therapy was developed in which craniotomy and immediate cranioplasty were performed simultaneously, the high rate of surgical site infections (0.5%–11%) has caused tremendous implanted mesh failure . In this situation, the mesh has to be removed, and the patient still needs the protection of temporary biomaterials.…”
Section: Introductionmentioning
confidence: 99%